(untitled) (Journal of Pure and Applied Sciences (Science Forum), 2026)
Regional fault systems evolve as a result of crustal movements of massive scale trailing for hundreds to thousands of kilometers across land and sea. The impact of these large-scale geologic structures within such provinces has resulted in the development of primary and secondary conduits, serving as pathways for the movement of mineralizing fluids. Such effects lead to ore deposit formations. The Nigerian regional fault systems trend ing NE-SW include the Anka–Zuru and Kalangai–Zungeru–Ifewara faults which traverse the entire western half of Nigeria, evident within the Neoproterozoic supracrustal low- to medium-grade metasediments. They are marked by a series of discontinuous quartzite ridges, mylonites, sheared, and cataclastic rocks of discrete bodies. Gold and rare-metal mineralization, however, evolved within associated hydrothermal fluids that exploited the conduits and precipitated within and associated subsidiaries. This paper looks at these regional faults as they act as the primary plumbing systems and points of economic min eralization. Concentrated mineralizing fluids enriched by valuable elements, ions, and metals are thus dispersed into various lithological and/or structural units through multiple subsidiary fractures/faults within the basement complex of Nigeria.